Synthesis and characterization of Silver/ Bentonite/ Starch bionanocomposite by green method: article - A. Rahman, Nur Ilmi Adila; Mulana, Farid (2018)
The aim of this research is to prepare silver nanoparticles (AgNPs) by using green reduction method. Bentonite (BTN), starch (Stc), D(+)-glucose and silver nitrate (AgNO3) were utilized and studied as solid support, stabilizer, green reducing agent and silver precursor respectively. Parameter involved is concentration of 10 mM, 50 mM, 100 mM, 150 mM of silver nitrate. It was found that the best concentration of silver nitrate is at 50 mM to synthesize bionanocomposite as according to UV-Vis result because it is just enough to reduce silver ions. Additional study of properties of bentonite has been made by varying the range of amount such as 1 g, 2 g, 3 g and 4 g of bentonite clay. The study showed that 4 g of bentonite produced the best absorbance peak hence proving that bentonite is a good solid support in bionanocomposite. The synthesized bionanocomposite is characterized by using Ultraviolet visible spectroscopy (UV-Vis), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM).